Pengaruh Kualitas Informasi dan Pengalaman Investasi Terhadap Niat Investasi Kripto - Norisnita, Muazila; Suhaya, Ifta Almazah (Forum Kerjasama Pendidikan Tinggi, 2025)
This study was conducted to identify the influence of Information Quality and Investment Experience on Cryptocurrency Investment Intention. The rapid development of technology and digitalization processes has driven significant transformations in the financial sector, particularly with the emergence of modern investment instruments such as crypto assets. The increasing number of investors in Indonesia highlights the importance of understanding the psychological and informational factors that influence individuals’ decisions to invest in cryptocurrencies. A quantitative method was employed in this study. Furthermore, the researcher distributed questionnaires to 354 respondents residing in Surabaya City who had prior investment experience. A multiple linear regression technique was applied with the assistance of SPSS version 25 software. The findings indicate that Information Quality and Investment Experience have a positive and significant influence on Cryptocurrency Investment Intention. This means that higher levels of information quality and investment experience positively affect individuals’ intentions to invest in crypto assets. Based on the Standardized Coefficients (Beta) values, the Information Quality variable shows an influence of 0.150, while the Investment Experience variable has a higher influence of 0.592, thus, Investment Experience plays a more dominant role compared to Information Quality in shaping cryptocurrency investment intention. The findings emphasize that practical experience in investing contributes more strongly to individuals’ intentions than merely relying on the quality of available information. Theoretically, this research enriches the literature on investment behavior in the digital era, while practically, it provides insights for financial industry players and digital asset platforms to enhance user education and experience, thereby promoting healthier and more sustainable investment intentions.